2021
DOI: 10.48550/arxiv.2106.14271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relaxation in Ordered Assembly of Magnetic Nanoparticles

Manish Anand

Abstract: We study the relaxation characteristics in the two-dimensional (l x × l y ) array of magnetic nanoparticles (MNPs) as a function of aspect ratio A r = l y /l x , dipolar interaction strength h d and anisotropy axis orientation using computer simulation. The anisotropy axes of all the MNPs are assumed to have the same direction, α being the orientational angle. Irrespective of α and A r , the functional form of the magnetization-decay curve is perfectly exponentially decaying with h d ≤ 0.2. There exists a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In a recent work, we have shown the relaxation time can be modulated by just varying the angle between the anisotropy axis and chain axis of MNPs [44]. In a another study, we have shown the Néel relaxation time can be enhanced or decreased by varying the anisotropy axes in the prefectly ordered system [45].…”
Section: Investigated the Anisotropy Axes Orientation Effect On The H...mentioning
confidence: 86%
“…In a recent work, we have shown the relaxation time can be modulated by just varying the angle between the anisotropy axis and chain axis of MNPs [44]. In a another study, we have shown the Néel relaxation time can be enhanced or decreased by varying the anisotropy axes in the prefectly ordered system [45].…”
Section: Investigated the Anisotropy Axes Orientation Effect On The H...mentioning
confidence: 86%
“…Therefore, these ordered nanoparticles ensembles provide a rich theoretical framework to study the role of dipolar interaction and magnetic anisotropy on magnetic response. Much research efforts ranging from experimental to theoretical modelling have been devoted to unearthing the magnetic properties in such versatile systems [33][34][35][36][37][38][39]. Deng et al presented a detailed and very informative overview regarding forming an anisotropic assembly of MNPs [33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, we studied the magnetic relaxation characteristics in the ordered assembly of nanoparticles using kinetic Monte Carlo simulation (kMC) with aligned anisotropy axes [39]. There is a fastening or slowing down of relaxation depending on the orientation of anisotropy axes with sufficient dipolar coupling strength.…”
Section: Introductionmentioning
confidence: 99%